Mapping and characterising electronic palliative care coordination systems and their intended impact: A national survey of end-of-life care commissioners. - Jacqueline Birtwistle; Pablo Millares-Martin; Catherine J Evans; Robbie Foy; Samuel Relton; Suzanne Richards; Katherine E Sleeman; Maureen Twiddy; Michael I Bennett; Matthew J Allsop (PLoS ONE, 2022)
Objectives In England, Electronic Palliative Care Coordination Systems (EPaCCS) were introduced in 2008 to support care coordination and delivery in accordance with patient preferences. Despite policy supporting their implementation, there has been a lack of rigorous evaluation of EPaCCS and it is not clear how they have been translated into practice. This study sought to examine the current national implementation of EPaCCS, including their intended impact on patient and service outcomes, and barriers and facilitators for implementation. Methods We conducted a national cross-sectional online survey of end-of-life care commissioning leads for Clinical Commissioning Groups (CCGs) in England. We enquired about the current implementation status of EPaCCS, their role in information sharing and intended impact, and requested routine patient-level data relating to EPaCCS. Results Out of 135 CCGs, 85 (63.0%) responded, with 57 (67.1%) having operational EPaCCS. Use of EPaCCS were confined to healthcare providers with most systems (67%) not supporting information sharing with care homes and social care providers. Most systems (68%) sought to facilitate goal concordant care, although there was inconsonance between intended impacts and monitoring measures used. Common challenges to implementation included healthcare professionals' limited engagement. Only one-third of patients had an EPaCCS record at death with limited recording of patient preferences. Conclusions Critical gaps exist in engagement with EPaCCS and their ability to facilitate information sharing across care providers. The limited alignment between stated goals of EPaCCS and their monitoring impedes efforts to understand which characteristics of systems can best support care delivery.